Respuesta :
Answer:
[tex]F(x)=4cos(x)-6sin(x)+4x+8[/tex]
Step-by-step explanation:
1. Write the expression.
[tex]f'(x)=-4sin(x)-6cos(x)+4[/tex]
2. Write the expression for the integral.
[tex]\int\((-4sin(x)-6cos(x)+4) \, dx[/tex]
3. Separate into multiple integrals.
[tex]\int\((-4sin(x)) \, dx+\int\((-6cos(x)) \, dx+\int\((4) \, dx[/tex]
4. Solve each integral.
• Check the attached image for a better understanding of these results.
[tex]\int\((-4sin(x)) \, dx=\\ \\-4\int\((sin(x)) \, dx=\\ \\-4(-cos(x))+C=\\ \\4cos(x)+C[/tex]
---------------------------------------------------------------------------------------------------------
[tex]\int\((-6cos(x)) \, dx=\\ \\-6\int\((cos(x)) \, dx=\\\\-6(sin(x))+C=\\ \\-6sin(x)+C[/tex]
---------------------------------------------------------------------------------------------------------
[tex]\int\((4) \, dx=\\ \\4x+C[/tex]
5. Sum up all the integrals.
[tex](4cos(x))+(-6sin(x))+(4x)+C\\ \\4cos(x)-6sin(x)+4x+C[/tex]
6. Write in standard form (solved for y).
[tex]y=4cos(x)-6sin(x)+4x+C[/tex]
7. Substitute the given values and solve for C.
[tex]12=4cos(0)-6sin(0)+4(0)+C\\ \\4cos(0)-6sin(0)+4(0)+C=12\\ \\C=12-4cos(0)+6sin(0)-4(0)\\ \\C=12-4(1)+6(0)-4(0)\\ \\C=12-4\\ \\C=8[/tex]
8. Express your result.
[tex]F(x)=4cos(x)-6sin(x)+4x+8[/tex]
---------------------------------------------------------------------------------------------------------
How to verify the result?
If the result is correct, then F(0)=12. Let's test it!
[tex]F(0)=4cos(0)-6sin(0)+4(0)+8=12[/tex]. Hence, the answer is correct.
---------------------------------------------------------------------------------------------------------
The graph.
I want to share the graph of this function, it looks pretty interesting. Check it out in attached image 2.
![Ver imagen Sprnt](https://us-static.z-dn.net/files/dbc/8beb3eb796c7dce9a4cc68ae6c2de06b.jpg)
![Ver imagen Sprnt](https://us-static.z-dn.net/files/db1/b41b7ed2bd95312e8d2acd83922b1d29.jpg)
Answer:
[tex]\text{f}(x)=4\cos(x)-6\sin(x)+4x+8[/tex]
Step-by-step explanation:
Given:
- [tex]\text{f}\:'(x)=-4 \sin(x)-6 \cos (x)+4[/tex]
- [tex]\text{f}(0)=12[/tex]
Fundamental Theorem of Calculus
[tex]\displaystyle \int \text{f}(x)\:\text{d}x=\text{F}(x)+\text{C} \iff \text{f}(x)=\dfrac{\text{d}}{\text{d}x}(\text{F}(x))[/tex]
If differentiating takes you from one function to another, then integrating the second function will take you back to the first with a constant of integration.
To find the function f(x), integrate f'(x) and use f(0) = 12 to find the value of the constant.
[tex]\begin{aligned}\displaystyle \int (-4 \sin(x)-6 \cos (x)+4)\:\:\text{d}x & = \int -4 \sin(x)\:\:\text{d}x -\int 6 \cos(x)\:\:\text{d}x+\int 4\:\:\text{d}x \\\\& =-4 \int \sin(x)\:\:\text{d}x -6\int \cos(x)\:\:\text{d}x +\int 4\:\:\text{d}x\\\\& = -4 \cdot -\cos(x)-6 \cdot \sin(x)+4x+\text{C}\\\\& = 4\cos(x)-6\sin(x)+4x+\text{C}\end{aligned}[/tex]
To find the value of C, substitute x = 0 into the function and set it to 12:
[tex]\begin{aligned}\text{f}(0) & =12\\\implies 4 \cos(0)-6\sin(0)+4(0)+\text{C} & =12\\4-0+0+\text{C} & =12\\4+\text{C} & = 12\\\text{C} & =8\end{aligned}[/tex]
Finally, substitute the found value of C into the equation:
[tex]\text{f}(x)=4\cos(x)-6\sin(x)+4x+8[/tex]
Rules of Integration
[tex]\boxed{\begin{minipage}{5 cm}\underline{Terms multiplied by constants}\\\\$\displaystyle \int ax^n\:\text{d}x=a \int x^n \:\text{d}x$\end{minipage}}[/tex]
If the terms are multiplied by constants, take them outside the integral.
[tex]\boxed{\begin{minipage}{5 cm}\underline{Integrating a constant}\\\\$\displaystyle \int n\:\text{d}x=nx+\text{C}$\\(where $n$ is any constant value)\end{minipage}}[/tex]
Just add an x to the constant.
[tex]\boxed{\begin{minipage}{6 cm}\underline{Integrating Trigonometric functions}\\\\$\displaystyle \int \sin(x)\:\text{d}x=- \cos (x)+\text{C}\\\\ \int \cos (x)\:\text{d}x=\sin(x)+\text{C}$\\\end{minipage}}[/tex]
Learn more about integration here:
https://brainly.com/question/27805589
https://brainly.com/question/28155016